Helicobacter pylorihas no influence on distal gastric cancer survival - Santos,Renata S. (2011)
CONTEXT: There is some evidence that Helicobacter pylori correlates with distal gastric cancer genesis. However, few studies analyzed the survival related to H. pylori infection. OBJECTIVE: To correlate gastric cancer survival and H. pylori infection. METHODS: Sixty-eight patients with distal gastric cancer that underwent subtotal gastrectomy were studied. Minimal follow-up was 1 month. H. pylori infection was confirmed by biopsy. RESULTS: Thirty-four patients (19 males (55.9%), mean age 60.9 ± 14.03, range 33-82 years) were H. pylori positive. Thirty-four patients (16 males (47.1%), mean age 57.9 ± 13.97, range 27-85 years) were H. pylori negative. Groups were comparable in regards to age (P = 0.4), gender (P = 0.5), stage [T (P = 0.2), N (P = 0.6) and M (P = 0.9)]. Survival was not different when groups were compared [P = 0.1616 (hazard ratio 0.6834, 95% CI 0.4009 to 1.1647)]. CONCLUSIONS: H. pylori infection does not affect distal gastric cancer survival.